Is the geography of food security in Sub-Saharan Africa changing? - Bloem, Jeffrey R.; Kyle, Jordan (CGIAR System Organization, 2025)
Recent global policy reports on food insecurity highlight two broad trends: (i) indicators of hunger are increasingly concentrated in fragile and conflict-affected countries and (ii) urban (and peri-urban) areas are home to a larger number of people who experience food insecurity than rural areas. Motivated by these trends, we investigate the extent to which these trends hold within countries in Sub-Saharan Africa by describing regional and within country patterns in the geographic distribution of indicators of food insecurity using harmonized household survey and conflict event data for 30 countries over the last two decades representing West, East, and Southern Africa. At the regional level, despite recent urbanization trends, we find that food insecurity remains largely concentrated in rural areas (relative to urban areas) both in terms of the population share and the number of people. Important heterogeneity persists at the country level. South Africa is a notable example where, since 2008, a larger number of people reporting food insecurity live in urban areas. This analysis highlights that the empirical findings motivating global policy narratives about the geography of food insecurity can critically hinge on data source choices and methodological analysis decisions, motivating more detailed analysis at the regional and national levels. We conclude by exploring the relationship between exposure to conflict and violence in both rural and urban areas to motivate discussion about future policy and research efforts to address food insecurity across a diverse set of contexts.